The educational platform and the motives of its use on students - Ahmed, Aliaa Ibrahim (Opción, 2019)
The study aimed to identify the motives of using the electronic educational platform for students of the library and information department at Imam Abdul Rahman bin Faisal University. As a result, 50.7% of students use the platform daily and 64.8% of the students believe that the platform achieved them the desired benefit. The researcher adopted an analytical descriptive case study using a questionnaire divided into 6 axes. In conclusion, the need to apply the electronic educational platform in many universities and colleges, provide training courses for students on how to keep their duties and assignments in the portfolio.